Dual Independent Rotor Axial Flux Induction Motor for Electric Vehicle Applications - Alireza Hesari; Ahmad Darabi; Fazel Pourmirzaei Deylami (IET Electrical Systems in Transportation)
This article proposes a dual independent rotor axial flux induction motor (DIR-AFIM) with two degrees of freedom as a propulsion motor for an electric vehicle (EV). The performance of this motor in different operating conditions of the vehicle is discussed and investigated. This motor has two rotors that are mechanically independent of each other, providing driving force for the EV separately and enabling the removal of any mechanical or electrical differential. The propulsion motor can play the role of differential and also reduce the cost and complexity of the entire propulsion system in some extent. The finite element modeling of the proposed motor has been performed and the performance characteristics have been evaluated in three operating scenarios: flat path, sloped path, and turning path, taking into account the dynamics of the vehicle. Additionally, the accuracy of the simulations and modeling has been confirmed by performing some practical tests on the prototype machine. The results show that the simulations and measurements are in good agreement and the proposed propulsion system can be a suitable option for lightweight electric vehicles.